HUBUNGAN POLA MAKAN DAN KARAKTERISTIK INDIVIDU DENGAN KEJADIAN HIPERTENSI PADA LANSIA DESA MERANTI PAHAM - Fipi Jayanti; Fitri Dian Nila Sari Sari; Siti Nurlani Harahap (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Hypertensionis high blood pressure which is synonymous with an increase in blood pressure beyond normal limits. A person is said to be hypertensive if the results of his systolic blood pressure measurement are ? 140 mmHg and his diastolic ? 90 mmHg. This study aims to determine whether there is a relationship between eating patterns and individual characteristics with the incidence of hypertension in the elderly in Hamlets III and IV, Meranti Paham Village, Labuhan Batu Regency, North Sumatra Province. The method used in this research is descriptive analytic method with cross sectional research design. From the research conducted, the results obtained were elderly who experienced hypertension (57.8%), elderly who did not experience hypertension (42.2%); the elderly who have a bad diet (45.3%), a good diet (54.7%); elderly male sex (59.4%), female (40.6%); the elderly have a low education level (96.9%), a high education level (3.1%); the elderly have a family history of hypertension (57.8%), the elderly have no family history of hypertension (42.2%). From the results of the study it can be concluded that there is a significant relationship between diet and the incidence of hypertension with a p value (0.000); there is a significant relationship between individual characteristics (gender) and the incidence of hypertension with a p value (0.000); there is no significant relationship between individual characteristics (level of education) and the incidence of hypertension with a p value (0.504); there is a significant relationship between individual characteristics (history of hypertension in the family) with the incidence of hypertension with a p value (0.000) 6%); the elderly have a low education level (96.9%), a high education level (3.1%); the elderly have a family history of hypertension (57.8%), the elderly have no family history of hypertension (42.2%). From the results of the study it can be concluded that there is a significant relationship between diet and the incidence of hypertension with a p value (0.000); there is a significant relationship between individual characteristics (gender) and the incidence of hypertension with a p value (0.000); there is no significant relationship between individual characteristics (level of education) and the incidence of hypertension with a p value (0.504); there is a significant relationship between individual characteristics (history of hypertension in the family) with the incidence of hypertension with a p value (0.000) 6%); the elderly have a low education level (96.9%), a high education level (3.1%); the elderly have a family history of hypertension (57.8%), the elderly have no family history of hypertension (42.2%). From the results of the study it can be concluded that there is a significant relationship between diet and the incidence of hypertension with a p value (0.000); there is a significant relationship between individual characteristics (gender) and the incidence of hypertension with a p value (0.000); there is no significant relationship between individual characteristics (level of education) and the incidence of hypertension with a p value (0.504); there is a significant relationship between individual characteristics (history of hypertension in the family) with the incidence of hypertension with a p value (0.000) 1%); the elderly have a family history of hypertension (57.8%), the elderly have no family history of hypertension (42.2%). From the results of the study it can be concluded that there is a significant relationship between diet and the incidence of hypertension with a p value (0.000); there is a significant relationship between individual characteristics (gender) and the incidence of hypertension with a p value (0.000); there is no significant relationship between individual characteristics (level of education) and the incidence of hypertension with a p value (0.504); there is a significant relationship between individual characteristics (history of hypertension in the family) with the incidence of hypertension with a p value (0.000) 1%); the elderly have a family history of hypertension (57.8%), the elderly have no family history of hypertension (42.2%). From the results of the study it can be concluded that there is a significant relationship between diet and the incidence of hypertension with a p value (0.000); there is a significant relationship between individual characteristics (gender) and the incidence of hypertension with a p value (0.000); there is no significant relationship between individual characteristics (level of education) and the incidence of hypertension with a p value (0.504); there is a significant relationship between individual characteristics (history of hypertension in the family) with the incidence of hypertension with a p value (0.000) From the results of the study it can be concluded that there is a significant relationship between diet and the incidence of hypertension with a p value (0.000); there is a significant relationship between individual characteristics (gender) and the incidence of hypertension with a p value (0.000); there is no significant relationship between individual characteristics (level of education) and the incidence of hypertension with a p value (0.504); there is a significant relationship between individual characteristics (history of hypertension in the family) with the incidence of hypertension with a p value (0.000) From the results of the study it can be concluded that there is a significant relationship between diet and the incidence of hypertension with a p value (0.000); there is a significant relationship between individual characteristics (gender) and the incidence of hypertension with a p value (0.000); there is no significant relationship between individual characteristics (level of education) and the incidence of hypertension with a p value (0.504); there is a significant relationship between individual characteristics (history of hypertension in the family) with the incidence of hypertension with a p value (0.000) 000); there is no significant relationship between individual characteristics (level of education) and the incidence of hypertension with a p value (0.504); there is a significant relationship between individual characteristics (history of hypertension in the family) with the incidence of hypertension with a p value (0.000) 000); there is no significant relationship between individual characteristics (level of education) and the incidence of hypertension with a p value (0.504); there is a significant relationship between individual characteristics (history of hypertension in the family) with the incidence of hypertension with a p value (0.000) Keywords:hypertension, elderly, diet, gender ABSTRACT Hypertension is high blood pressure exceeds normal limits. Someone is said to be hypertension if the result is systolic blood pressure ? 140 mmHg and diastolic ? 90 mmHg. This research is to determine the relationship between habits and individual characteristics with cases of hypertension in hamlet III and IV Meranti Paham, Labuhan Batu, North Sumatra. The research method was descriptive analytic with a cross-sectional design. The result was elderly with hypertension (57.8%), elderly not hypertension (42.2%); elderly with bad eating habits (45.3%), elderly with not bad eating habits (54.7%); elderly male (59.4%), elderly female (40.6%); elderly with low education level (96.9%), elderly with high education level (3.1%); elderly with genetic hypertension (57.8%), elderly do not have genetic hypertension (42.2%). The conclusions of the research results are a significant relationship between habits and individual characteristics with cases of hypertension (p value 0.000); there was a significant relationship between individual characteristics (gender) and cases of hypertension (p value 0.000); there was no significant relationship between individual characteristics (level of education) and cases of hypertension (p value 0.504); there was a significant relationship between individual characteristics (genetic) and cases of hypertension (p value 0.000). 000); there was no significant relationship between individual characteristics (level of education) and cases of hypertension (p value 0.504); there was a significant relationship between individual characteristics (genetic) and cases of hypertension (p value 0.000). 000); there was no significant relationship between individual characteristics (level of education) and cases of hypertension (p value 0.504); there was a significant relationship between individual characteristics (genetic) and cases of hypertension (p value 0.000).